Transparency and Accountability of BLT-DD Management during the Covid-19 Pandemic in Indonesia - Dinda Reskiana Putri; Haliah Haliah; Nirwana Nirwana (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
Direct cash transfer (BLT-DD) is a social assistance program that aims to help people in need, especially during the Covid-19 pandemic. transparency and accountability are both very important things in managing BLT-DD so that the program can run well, effectively, and efficientl. This systematic literature review research aims to determine whether the management of Direct Cash Assistance (BLT-DD) has been transparent and accountable. The method of writing a systematic literature review article goes through 5 stages starting from the problem formulation stage to the analysis stage and understanding the results of previous research. The literature search process is used by the library search method which is sourced from online media such as Google Scholar. The results of the systematic literature review of 12 articles used as references show show that the majority of BLT-DD management has been carried out with transparency and accountability. However, some research results state that its management cannot be said to be maximally accountable and transparent because there are still some shortcomings in its implementation. This should be a concern for village governments to improve the human resources of village officials and their accountability reporting in order to create accountable and transparent management of public funds